First total synthesis of hunanamycin A - Shingare, Rahul D.; Velayudham, R.; Gawade, Jalindar R.; Reddy, D. Srinivasa (Organic Letters, 2013)
The first total synthesis of hunanamycin A, an antibiotic natural product with a pyrido[1,2,3-de]quinoxaline-2,3-dione core from a marine-derived Bacillus hunanensis, is disclosed. The present effort provides access to sufficient amounts of scarce hunanamycin A for further biological evaluation and confirmation of the assigned absolute configuration. In addition, four new analogues of the natural product are reported.

Chiral aziridine ring opening: facile synthesis of (R)-modletine and (R)-phenoxybenzamine hydrochloride - Viswanadh, N.; Velayudham, R.; Jambu, S.; Sasikumar, M.; Muthukrishnan, Murugan (Tetrahedron Letters, 2015)
A simple and efficient synthesis of chiral drugs (R)-mexiletine 1, an anti-arrhythmic drug and (R)-phenoxybenzamine hydrochloride 2, an anti-hypertensive drug has been described via controlled reductive ring opening of chiral aziridine as a key step. The target compounds 1 and 2 were obtained in overall yields of 34% and 10.5%, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Aziridine; Mexiletine; Phenoxybenzamine

Transition metal free regio-selective C–H hydroxylation of chromanones towards the synthesis of hydroxyl-chromanones using PhI(OAc)2 as the oxidant - Viswanadh, N. (Chemical Communications, 2018)
The chromanone scaffold is considered as a privileged structure in drug discovery. Herein, we report a highly efficient PhI(OAc)2 mediated regioselective, direct C–H hydroxylation of chromanones. This method offers easy access to substituted 6-hydroxy chromanones in moderate to good isolated yields, thus paving the way for their pharmaceutical studies.